Semiconductive shielding material with high stripping property and low resistivity for high voltage cable and preparation method thereof
By using specific ratios of ethylene propylene ternary rubber, ethylene-vinyl acetate copolymer, low-density polyethylene, conductive carbon black, fluorine-containing silicone anti-binder and functional additives in the semiconductor shielding materials of high-voltage cables, the solution is solved The problem of easy damage to existing materials during peeling is achieved, and the effects of high peelability and low volume resistivity are achieved.
Patent Information
- Application Number
- CN202310478146.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-04-28
AI Technical Summary
The semiconductor shielding materials of existing high-voltage cables are prone to damage or tear during peeling, and are costly and have poor physical, chemical or mechanical properties.
A semiconductor shielding material with high peelability and low volume resistivity is adopted, and the composition includes 20-45 parts of ethylene propylene ternary rubber, 30-50 parts of ethylene-vinyl acetate copolymer, 15-20 parts of low-density polyethylene, 25-35 parts of conductive carbon black, 2-5 parts of fluorine-containing silicone anti-binder and 15-20 parts of functional additives. Through specific preparation methods and raw material ratios, the peelability and mechanical properties of the material are improved.
The high peelability and low volume resistivity of the high-voltage cable semiconductor shielding material are achieved, avoiding the phenomenon of damaging the insulating layer during the peeling process, while reducing the cost of the material and improving its physical, chemical and mechanical properties.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004206188980000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable materials, in particular to a semi-conductive shielding material with high stripping properties and low resistivity for high-voltage cables and a preparation method thereof. Background Art
[0002] High-voltage cable transmission has the characteristics of long distance, large capacity and low loss. It is the core electrical equipment for urban power transmission, cross-river and offshore power transmission, and is known as the "blood vessels" of the national economy. The voltage level and transmission capacity of high-voltage cables are constantly improving. As of 2019, the operating mileage of 66kV and above high-voltage AC cables has reached 86,000 km, and is developing rapidly at an annual growth rate of 7%; according to the national energy planning forecast, by 2050, my country's total social electricity consumption will double, and the operating mileage of high-voltage AC cables will exceed 200,000 km. In recent years, my country has achieved a leapfrog development of high-voltage DC cables from ±160kV to ±500kV in voltage level, and the construction of DC cable transmission projects has entered a period of rapid development.
[0003] As an indispensable component of high-voltage cables, the semi-conductive shielding layer is tightly surrounded by the inner and outer insulation layers through three-layer co-extrusion technology. The inner and outer semi-conductive layers form equal potentials with the cable conductor and the metal shielding layer, respectively, so that a smooth interface is formed between the insulation layer and the high voltage potential and the ground potential, which plays a role in eliminating burrs or protrusions on the surface of the metal conductor, uniforming the interface electric field distribution, suppressing excessive local field strength, and preventing local discharge.
[0004] In order to facilitate the splicing of cables or the manufacture of cable ends, the outer semiconducting shielding layer should be able to be easily peeled off from the insulating layer, and when peeled off, only a small amount of conductor or no trace of conductor is left to adhere to the main insulating layer, and the surface of the main insulating layer will not be damaged. However, the outer semiconducting shielding layer should be completely bonded to the main insulating layer when used. In this way, when the cable is installed and generally used, the two layers of material will not separate, and impurities such as air and water will not enter between the two layers of material.
[0005] Composite layers bonded together by the main insulating layer material and the semiconductor shielding layer material (the materials of the composite layer have the desired mutual bonding and peeling properties) have been greatly developed and have been commercially applied. However, such laminated composite materials still have their disadvantages. Generally speaking, the semiconductor materials used are relatively expensive and have poor physical, chemical or mechanical properties. In addition, if the semiconductor shielding layer used is relatively hard, it is difficult to peel it off from the main insulating layer. A manual tool must be used to cut through the semiconductor shielding layer and cut it to the main insulating layer in order to peel it off smoothly. Such a peeling method may damage the outer surface of the main insulating layer; if the semiconductor shielding layer is relatively soft, it may be torn when it is peeled off from the main insulating layer. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a semi-conductive shielding material with high stripping properties and low volume resistivity for high-voltage cables and a preparation method thereof.
[0007] A semi-conductive shielding material with high stripping property and low volume resistivity for high-voltage cables comprises the following components by weight: 20-45 parts of ethylene propylene diene monomer (EPDM), 30-50 parts of ethylene-vinyl acetate copolymer (EVA), 15-20 parts of low-density polyethylene (LDPE), 25-35 parts of conductive carbon black, 2-5 parts of fluorine-containing silicon anti-adhesive agent and 15-20 parts of functional additives; wherein the fluorine-containing silicon anti-adhesive agent has a structure as shown in Formula I:
[0008]
[0009] In formula I, n and m are both integers, and n=2-5, and m=6-8.
[0010] In some embodiments of the present invention, the preparation method of the fluorine-containing silicon anti-adhesive agent comprises the following steps: S1: placing a reactor filled with an inert gas in an ice water bath, then adding a fluorine-containing alkyl alcohol polyether having a structure of formula II, propylene glycol and a solid acid catalyst, slowly heating up to start the reaction, and after the reaction is completed, adding a water absorbent and filtering;
[0011]
[0012] Wherein, n and m in formula II are both integers, and n=2-5, m=6-8;
[0013] S2: placing the product obtained in step S1 and the solid acid catalyst in another reactor filled with nitrogen, heating up again to start the reaction, and after the reaction is completed, adding a water absorbent and filtering;
[0014] S3: Fill the reactor in an ice-water bath with inert gas, then put the product obtained in step S2 and the catalyst into the reactor, heat it to the reaction temperature, slowly drop trimethoxysilane, keep it warm for a while, and after the reaction is completed, collect the fraction at 278-280°C by reduced pressure distillation, which is the target product.
[0015] As the raw material for preparing the new fluorinated silicone anti-adhesive agent, the perfluoropolyether chain segment contained in the fluorinated alkyl alcohol molecule should not be too long. The reason is that although the polyether chain segment will enhance the flexibility and elongation at break of the semi-conductive shielding material, the inventors found in the experiment that the overly long perfluoropolyether chain segment will make the anti-adhesive agent unable to achieve sufficient uniform dispersion and contact when melt blending with other components, which will eventually lead to the stripping and mechanical properties of the prepared semi-conductive shielding material unable to meet the application requirements. In summary, the degree of polymerization of the fluorinated polyether chain segment in the fluorinated alkyl alcohol polyether molecule used should be controlled at n=2-5 and m=6-8.
[0016] In some embodiments of the present invention, the molar ratio of the fluorinated alkyl alcohol polyether to propylene glycol in step S1 is 1:2-2.2.
[0017] In some embodiments of the present invention, the solid acid catalyst in step S1 is at least one of aluminum oxide, manganese oxide, and iron oxide; and the reaction temperature is 240-280° C. Alcohol organics undergo intramolecular dehydration to generate alkenyl or intermolecular dehydration to generate ether bonds under high temperature and acid catalysis. Studies have shown that the temperature required for intramolecular dehydration of alcohol organics is higher than the temperature for intermolecular dehydration. Therefore, when preparing the fluorine-containing silicon anti-adhesive agent in the present invention, the reaction temperature in step S1 is preferably controlled at 240-280° C., and the reaction conditions in step S2 are 300-350° C.
[0018] In some embodiments of the present invention, the water absorbing agent used is at least one of calcium oxide, calcium chloride, anhydrous magnesium sulfate and silicon dioxide.
[0019] In some embodiments of the present invention, in step S3, the catalyst used is obtained by reacting chloroplatinic acid with isopropanol and citric acid in a mass ratio of 5:1-2:1-2 at 50-60°C; the molar ratio of the product obtained in step S2 to trimethoxysilane is 1:2-2.5.
[0020] In some embodiments of the present invention, in step S3, the dripping time of trimethoxysilane is controlled between 0.5-1h, the reaction temperature is 80-85°C, and the reaction time is 2-3h. During the dripping and reaction, the temperature and time must be well controlled. If the temperature is too high or the time is too long, the proportion of side reactions in the system will increase, resulting in a decrease in the yield of the target product.
[0021] In some embodiments of the present invention, the oil absorption value of the conductive carbon black is 150-350ml / 100g, and the particle size is not higher than 30nm. Studies have shown that the higher the oil absorption value of the conductive carbon black, the stronger the hydrophobicity, the worse the wettability and dispersibility, the greater the surface tension and viscosity of the slurry, and its conductivity will also be affected. During the experimental stage of the present invention, the inventors found that the oil absorption value of the conductive carbon black used needs to be adapted to the semi-conductive shielding material. If the oil absorption value of the conductive carbon black is too low, if a certain volume resistivity is to be achieved, more conductive carbon black needs to be added, and excessive conductive carbon black will cause the viscosity of the semi-conductive shielding material to increase, which is not conducive to processing and production. If the oil absorption value of the conductive carbon black is too high, only a small amount is needed to achieve the required low volume conductivity, but due to the poor dispersibility of the conductive carbon black with high oil absorption value, its distribution in the material is uneven, affecting the final performance of the material. Therefore, preferably, when the oil absorption value of the conductive carbon black is 150-200 ml / 100 g, its particle size should be controlled at 20-30 nm, and when the oil absorption value of the conductive carbon black is 200-350 ml / 100 g, its particle size should be controlled at 15-20 nm. Specific choices may be, but are not limited to: Cabot VXC72, VXC305, VXC605, BP2000.
[0022] In some embodiments of the present invention, the functional additives include a lubricant, a vulcanization activator, a crosslinking agent and an antioxidant.
[0023] In some embodiments of the present invention, the lubricant is paraffin, specifically one of microcrystalline paraffin, liquid paraffin, polyethylene wax, and semi-refined paraffin; the vulcanization activator is at least one of zinc oxide and stearic acid, the cross-linking agent is at least one of diisopropyl peroxide (DCP) and triallyl isocyanurate (TAIC), and the antioxidant is at least one of antioxidant D, antioxidant RD, antioxidant 124, antioxidant MB, antioxidant DNP, and antioxidant NBC.
[0024] A preparation method of a semi-conductive shielding material comprises the following steps: firstly, EPDM rubber, ethylene-vinyl acetate copolymer, conductive carbon black and functional additives are put into a twin-screw extruder at 150-200°C according to certain weight parts for melt blending to obtain a masterbatch; then, the masterbatch is melt blended with a certain weight parts of low-density polyethylene and a fluorine-containing silicon anti-adhesive agent at 180-250°C for extrusion into granules; and then, the semi-conductive shielding material is obtained by press molding.
[0025] Beneficial effects: Compared with the prior art, the present invention adds a new type of anti-adhesive agent with ether bonds and carbon-fluorine bonds to the semi-conductive shielding material, which gives the material the required surface tension and mechanical properties, making it highly removable. When the cable composite layer is disassembled, it is easy to peel off without damaging the insulating layer. By adjusting the oil absorption value and particle size of the conductive carbon black used and the compatibility with the other raw materials, the conductive carbon black with a suitable oil absorption value can be evenly dispersed in the raw material system, thereby obtaining a conductive carbon black with a volume conductivity of not more than 3.0×10 2 Ω·cm semi-conductive shielding material. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the embodiments. It should be noted that the following embodiments and comparative examples are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various improvements within the concept of the present invention may be carried out without departing from the gist or scope of the present invention.
[0027] The following is an exemplary description of the preparation of the fluorine-containing silicon anti-adhesive agent used in each embodiment:
[0028] Anti-adhesive agent-1
[0029] S1: Place a reactor filled with nitrogen in an ice water bath, then add a fluorinated alkyl alcohol polyether having a structure of formula II-1 and propylene glycol in a molar ratio of 1:2, and simultaneously add alumina as a catalyst, slowly raise the temperature to 240°C to start the reaction, and after the reaction is completed, add calcium oxide and filter;
[0030]
[0031] S2: placing the product obtained in step S1 and aluminum oxide in another reactor filled with nitrogen, heating to 300°C again to start the reaction, and after the reaction is completed, adding calcium oxide and filtering;
[0032] S3: Fill the reactor in an ice-water bath with nitrogen, then put the product obtained in step S2 and the catalyst into the reactor, heat it to 80°C, slowly add trimethoxysilane dropwise for 0.5h; keep warm for a period of time, react for 2-3h, and collect the fraction at 278-280°C by reduced pressure distillation, which is the target product, as shown in formula I-1; wherein the catalyst used is chloroplatinic acid, isopropanol, and citric acid reacted at a mass ratio of 5:1:1 at 50°C, and the molar ratio of the product obtained in step S2 to trimethoxysilane is 1:2.
[0033]
[0034] Anti-adhesive agent-2
[0035] S1: Place a reactor filled with nitrogen in an ice water bath, then add a fluorinated alkyl alcohol polyether having a structure of formula II-2 and propylene glycol in a molar ratio of 1:2.1, and simultaneously add alumina as a catalyst, slowly raise the temperature to 250°C to start the reaction, and after the reaction is completed, add anhydrous magnesium sulfate and filter;
[0036]
[0037] S2: placing the product obtained in step S1 and alumina in another reactor filled with nitrogen, heating to 320°C again to start the reaction, and after the reaction is completed, adding anhydrous magnesium sulfate and filtering;
[0038] S3: Fill the reactor in an ice-water bath with nitrogen, then put the product obtained in step S2 and the catalyst into the reactor, heat it to 85°C, slowly add trimethoxysilane dropwise for 0.8h; keep warm for a period of time, react for 2-3h, and collect the fraction at 278-280°C by reduced pressure distillation, which is the target product, as shown in formula I-2; wherein the catalyst used is chloroplatinic acid, isopropanol, and citric acid reacted at a mass ratio of 5:1:2 at 60°C, and the molar ratio of the product obtained in step S2 to trimethoxysilane is 1:2.3.
[0039]
[0040]
[0041] Anti-adhesive-3
[0042] S1: Place a reactor filled with nitrogen in an ice water bath, then add a fluorinated alkyl alcohol polyether having a structure of formula II-3 and propylene glycol in a molar ratio of 1:2.2, and simultaneously add alumina as a catalyst, slowly raise the temperature to 280°C to start the reaction, and after the reaction is completed, add calcium chloride and filter;
[0043]
[0044] S2: placing the product obtained in step S1 and alumina in another reactor filled with nitrogen, heating to 350°C again to start the reaction, adding calcium chloride and filtering after the reaction is completed;
[0045] S3: Fill the reactor in an ice-water bath with nitrogen, then put the product obtained in step S2 and the catalyst into the reactor, heat it to 85°C, slowly add trimethoxysilane dropwise for 1 hour; keep warm for a period of time, react for 2-3 hours, and collect the fraction at 278-280°C by reduced pressure distillation, which is the target product, as shown in formula I-3; wherein the catalyst used is chloroplatinic acid, isopropanol, and citric acid reacted at a mass ratio of 5:2:2 at 60°C, and the molar ratio of the product obtained in step S2 to trimethoxysilane is 1:2.5.
[0046]
[0047] Anti-adhesive-4
[0048] The preparation method is similar to that of anti-adhesive agent-1, except that the structure of the fluorinated alkyl alcohol polyether used is as shown in Formula II-4:
[0049]
[0050] The structure of the obtained anti-adhesive agent-4 is as shown in Formula I-4:
[0051]
[0052] The preparation method of the semi-conductive shielding material in each embodiment and comparative example is as follows: first, EPDM rubber, ethylene-vinyl acetate copolymer, conductive carbon black and functional additives are put into a twin-screw extruder at 150-200°C according to a certain weight portion and melt blended to obtain a masterbatch, and then the masterbatch is melt blended with a certain weight portion of low-density polyethylene and fluorine-containing silicon anti-adhesive agent at 180-250°C and extruded into granules, and then press-formed to obtain the semi-conductive shielding material, wherein the unspecified operating conditions are carried out according to the known technology in the art. The raw materials and proportions used in each embodiment and comparative example are specifically shown in Table 1-1 and Table 1-2:
[0053] Table 1-1 Raw materials and proportions used in Example 1-3
[0054]
[0055] Table 1-2 Raw materials and proportions used in Examples 4-5 and Comparative Examples 1-2
[0056]
[0057]
[0058] The conductive carbon black used in Example 4 is Czech conductive carbon black CHEZACARB AC80, which has an oil absorption value of 400 ml / 100 g and a particle size of 20-25 nm; the conductive carbon black used in Example 5 is Tianjin Huayuan's HY7750, which has an oil absorption value of 120±2 ml / 100 g and a particle size of 20-25 nm.
[0059] The peelability and mechanical properties of the semiconductive shielding materials obtained in the above Examples 1-5 and Comparative Examples 1-2 were tested, and the results are shown in Table 2:
[0060] Table 2 Test data of semiconductive shielding materials obtained in Examples 1-5 and Comparative Examples 1-2
[0061]
[0062] It can be seen from the test data in Table 2 that when the oil absorption value of the conductive carbon black used in the semi-conductive shielding material is too high or too low (Example 4 and Example 5), its conductivity, tensile strength and peel strength are somewhat different from the performance in Examples 1-3; if the fluorine-containing silicone anti-adhesive agent used in the preparation contains a longer fluorine-containing polyether chain segment in the molecule (Comparative Example 1), the tensile strength and elongation of the semi-conductive shielding material are reduced, and its peel force is significantly increased; the conductivity, peelability and mechanical properties of the semi-conductive shielding material without the addition of the fluorine-containing silicone anti-adhesive agent all fail to meet the standard range.
[0063] In summary, the semi-conductive shielding material provided by the present invention has excellent electrical conductivity, satisfactory mechanical properties and good peelability.
Claims
1. A semi-conductive shielding material with high stripping properties and low volume resistivity for high voltage cables, characterized in that: The composition comprises the following components by weight: 20-45 parts of EPDM rubber, 30-50 parts of ethylene-vinyl acetate copolymer, 15-20 parts of low-density polyethylene, 25-35 parts of conductive carbon black, 2-5 parts of fluorine-containing silicon anti-adhesive agent and 15-20 parts of functional additives; wherein the fluorine-containing silicon anti-adhesive agent has a structure as shown in Formula I: ; In formula I, n and m are both integers, and n=2-5, m=6-8; The conductive carbon black has an oil absorption value of 150-350 ml / 100 g and a particle size of no more than 30 nm.
2. The semiconductive shielding material according to claim 1, characterized in that: The preparation method of the fluorine-containing silicon anti-adhesive agent comprises the following steps: S1: placing a reactor filled with inert gas in an ice water bath, then adding a fluorinated alkyl alcohol polyether having a structure of formula II, propylene glycol and a solid acid catalyst, slowly raising the temperature to start the reaction, and after the reaction is completed, adding a water absorbent and filtering; ; S2: placing the product obtained in step S1 and the solid acid catalyst in another reactor filled with inert gas, heating up again to start the reaction, and after the reaction is completed, adding a water absorbent and filtering; S3: Fill the reactor in an ice-water bath with inert gas, then put the product obtained in step S2 and the catalyst into the reactor, heat it to the reaction temperature, slowly drop trimethoxysilane, keep it warm for a while, and after the reaction is completed, collect the fraction at 278-280°C by reduced pressure distillation, which is the target product.
3. The semiconductive shielding material according to claim 2, characterized in that: In the step S1, the molar ratio of the fluorinated alkyl alcohol polyether to propylene glycol is 1:2-2.
2.
4. The semiconductive shielding material according to claim 2, characterized in that: The catalyst in step S1 is a solid acid catalyst which is at least one of aluminum oxide, manganese oxide and iron oxide; and the reaction temperature is 240-280°C.
5. The semiconductive shielding material according to claim 2, characterized in that: The reaction temperature in step S2 is 300-350°C.
6. The semiconductive shielding material according to claim 2, characterized in that: In the step S3, the catalyst used is obtained by reacting chloroplatinic acid with isopropanol and citric acid at a mass ratio of 5:1-2:1-2 at 50-60°C; the molar ratio of the product obtained in step S2 to trimethoxysilane is 1:2-2.
5.
7. The semiconductive shielding material according to claim 2, characterized in that: In step S3, the dripping time of trimethoxysilane is controlled between 0.5-1 h, the reaction temperature is 80-85° C., and the reaction time is 2-3 h.
8. The semiconductive shielding material according to claim 1, characterized in that: The functional additives include a lubricant, a vulcanization activator, a crosslinking agent and an antioxidant; wherein the lubricant is paraffin, the vulcanization activator is at least one of zinc oxide and stearic acid, the crosslinking agent is at least one of diisopropyl peroxide and triallyl isocyanurate, and the antioxidant is at least one of antioxidant D, antioxidant RD, antioxidant 124, antioxidant MB, antioxidant DNP, and antioxidant NBC.
9. The method for preparing the semiconductive shielding material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: firstly, EPDM rubber, ethylene-vinyl acetate copolymer, conductive carbon black and functional additives are put into a twin-screw extruder at 150-200°C according to certain weight proportions for melt blending to obtain a masterbatch; then, the masterbatch is melt blended with a certain weight proportion of low-density polyethylene and a fluorine-containing silicon anti-adhesive agent at 180-250°C for extrusion into granules; and then, the semi-conductive shielding material is obtained by pressurizing and molding.
Citation Information
Patent Citations
Easy-to-peel semiconductive insulation shielding material for power cable and preparation method of easy-to-peel semiconductive insulation shielding material
CN105348631A
Thermoplastic strippable semiconductive shielding material for environment-friendly power cable insulation and preparation method thereof
CN111303516A